STRENGTHENING ICT AND GOVERNANCE TO ACHIEVE 2030 SDGs: : Lesson Learnt From Ridwan Kamil and Community Initiative - Nina Widyawati; Sri Sunarti Purwaningsih (LIPI Press, 2022)
Achievement of 2030 SDGs is the commitment of many countries, including South East Asian countries and Indonesia in particular. Indonesia as other South East Asian countries has been doing a great effort to achieve the 2030 SDGs. Among other goals, Goal 9 that related to industry, innovation and infrastructure in which information and communication technologies is an important way to faciltate sustainable development. This is in line with the Industrial Revolution 4.0. Well established Information and Communication Technology (ICT) and governance that is involved local govenment and civil society. Bandung, West Java Indonesia, is one of the good example of the smart city when it was Ridwan Kamil (RK) as the Mayor. RK, the former mayor of Bandung who used ICT as the tool to improve public services with the use of e-aplications. RK also communicate directly with his community members through social media account initiated by a civil society (RK Watch). Interactive activities through ICT, especially social media are able to accelerate public services. Most issues raise on this account concerning to the delay in responding public services related to the target of SDGs namely infrastructure, environment, health and population administration. This paper will discuses some issues on how ICT able to cut beaucratic line and to accelarate public services; negotiation between lovers and haters in relation to public sevice priorities; type of public services related to SDG’s topic. Data used for this paper drawn from our research collected by using a set of qualitative approach and methods such as indepth interviews and focus group discussions.